Structural Variants May Be a Source of Missing Heritability in sALS - Theunissen, Frances; Flynn, Loren L.; Anderton, Ryan S.; Mastaglia, Frank; Pytte, Julia; Jiang, Leanne; Hodgetts, Stuart; Burns, Daniel K.; Saunders, Ann; Fletcher, Sue; Wilton, Steve D.; Akkari, Patrick Anthony (Frontiers in Neuroscience, 2020)
The underlying genetic and molecular mechanisms that drive amyotrophic lateral sclerosis remain poorly understood. Structural variants within the genome can play a significant role in neurodegenerative disease risk, such as the repeat expansion in C9ORF72 and the tri-nucleotide repeat in ATXN2, both of which are associated with familial and sporadic amyotrophic lateral sclerosis. Many such structural variants reside in uncharacterized regions of the human genome, and have been under studied. Therefore, characterisation of structural variants located in and around genes associated with amyotrophic lateral sclerosis could provide insight into disease pathogenesis, and lead to the discovery of highly informative genetic tools for stratification in clinical trials. Such genomic variants may provide a deeper understanding of how gene expression can affect disease aetiology, disease severity and trajectory, patient response to treatment, and may hold the key to understanding the genetics of sporadic amyotrophic lateral sclerosis.This article outlines the current understanding of amyotrophic lateral sclerosis genetics and how structural variations may underpin some of the missing heritability of this disease.